FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN TANGKAP DI DESA TABANIO KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - MUHAMMAD SAILLUDDIN (PPJP Universitas Lambung Mangkurat, 2018)
This research was conducted to know: the cost factor of care, operational cost, depreciation cost and the means of catching together to income and know the most dominant factor influence the catching fisherman income in Tabanio Village, Takisung Sub-District, Tanah Laut Regency.This thesis research uses quantitative method with numbers such as maintenance cost, operational cost, fishing gear and depreciation cost. Meanwhile, the data used to analyze the thesis is using cross section data. With primary material that is taken a direct data from source, that is obtained from direct interviews from fishing boat owner in Tabanio Village, Takisung District, Tanah Laut Regency.After doing research, it is known that simultaneously the cost factor of care, operational cost, depreciation cost and fishing gear have an effect on to catch fisherman income and appliance catch variable (X3) is the factor which has the most dominant influence to catch fisherman's income in Tabanio Village, Takisung District Tanah Laut District.Keywords:: Maintenance Cost, Operational Cost, Depreciation Cost, Fisherman's Income Catch